Parameters of two-channel five-zone dielectric structure for experiments on wakefield acceleration in KIPT - Zaleskyi, D.Yu.; Sotnikov, G.V. (Вопросы атомной науки и техники, 2018)
The computations results of the parameters of a two-channel five-zone rectangular dielectric structure for the
experimental test of basic principles of using such structures for wakefield acceleration are presented. The structure
consists of two adjacent vacuum channels (one for the drive bunches, the other for the accelerated bunch) bordered
by dielectric slabs. The entire structure is placed in a rectangular waveguide. In the work is also investigated the
tolerances for parameters of the structure that affect the value of the transformer ratio and the accelerating gradient. Представлено параметри двоканальної п’ятизонної прямокутної діелектричної структури з метою
експериментальної перевірки основних принципів використання таких структур для кільватерного прискорення.
П’ятизонна двоканальна діелектрична структура складається із двох сусідніх вакуумних каналів (один для
ведучого згустка, інший для згустків, що прискорюються), оточених діелектричними пластинами. Уся структура
поміщена в прямокутний хвилевід. Також досліджено допустимі відхилення параметрів структури, які впливають
на величину коефіцієнта трансформації та прискорюючого градієнта. Представлены параметры двухканальной пятизонной прямоугольной диэлектрической структуры с
целью экспериментальной проверки основных принципов использования таких структур для кильватерного
ускорения. Пятизонная двухканальная диэлектрическая структура состоит из двух соседних вакуумных
каналов (один для ведущего сгусткa, другой для ускоряемых сгустков), окруженных диэлектрическими
пластинами. Вся структура помещена в прямоугольный волновод. Tакже исследуются допуски на
параметры структуры, которые влияют на величину коэффициента трансформации и ускоряющего
градиента.